2004
DOI: 10.1007/s00425-003-1193-2
|View full text |Cite
|
Sign up to set email alerts
|

Microtubules and microfilaments coordinate to direct a fountain streaming pattern in elongating conifer pollen tube tips

Abstract: This study investigates how microtubules and microfilaments control organelle motility within the tips of conifer pollen tubes. Organelles in the 30-microm-long clear zone at the tip of Picea abies (L.) Karst. (Pinaceae) pollen tubes move in a fountain pattern. Within the center of the tube, organelles move into the tip along clearly defined paths, move randomly at the apex, and then move away from the tip beneath the plasma membrane. This pattern coincides with microtubule and microfilament organization and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 30 publications
6
48
1
Order By: Relevance
“…As shown in Figure 10A (see also Supplemental Video 1), cytoplasm in control tubes streams in a fountain pattern or, rarely, in a reverse fountain pattern, similar to a previous report in Picea abies pollen tubes (Justus, et al, 2004). In contrast, the direction and speed of cytoplasmic streaming in MG132-treated tubes was markedly affected in a time-dependent manner.…”
Section: Mg132 Treatment Disrupts Cytoskeleton Organization and Cytopsupporting
confidence: 89%
See 2 more Smart Citations
“…As shown in Figure 10A (see also Supplemental Video 1), cytoplasm in control tubes streams in a fountain pattern or, rarely, in a reverse fountain pattern, similar to a previous report in Picea abies pollen tubes (Justus, et al, 2004). In contrast, the direction and speed of cytoplasmic streaming in MG132-treated tubes was markedly affected in a time-dependent manner.…”
Section: Mg132 Treatment Disrupts Cytoskeleton Organization and Cytopsupporting
confidence: 89%
“…To further confirm the MG132-induced disruption of the cytoskeleton, confocal microscopy was used to visualize the cytoplasmic streaming in pollen tubes, a phenomenon that depends on intact cytoskeleton elements, especially actin microfilaments (Taylor and Hepler, 1997;Li et al, 2001;Justus, et al, 2004). As shown in Figure 10A (see also Supplemental Video 1), cytoplasm in control tubes streams in a fountain pattern or, rarely, in a reverse fountain pattern, similar to a previous report in Picea abies pollen tubes (Justus, et al, 2004).…”
Section: Mg132 Treatment Disrupts Cytoskeleton Organization and Cytopsupporting
confidence: 77%
See 1 more Smart Citation
“…22,23 In plant cells, however, vesicles are transported along actin fibers by myosin motor molecules. [24][25][26][27] Fan et al labeled the endocytic vesicles using the fluorescent membrane dye FM4-64 to observe whether cadmium treatment influenced endocytosis and vesicular transport in root hair cells. 15 Their time-lapse images of cadmium-treated root hairs showed that the FM dye staining pattern was obviously distinct from that of control cells, suggesting that membrane endocytosis and vesicular trafficking were perturbed during cadmium stress and this perturbation might result from the cadmium-induceddisruption of the "tracks" (actin filaments) for vesicle transport (Fig.…”
Section: Cadmium and Vesicular Traffickingmentioning
confidence: 99%
“…In many angiosperm pollen tubes, disruption of the MTs has no apparent effect on growth (Cai and Cresti, 2010), but it has recently been reported to affect both endocytosis and exocytosis in the tip of tobacco (Nicotiana tabacum) pollen tubes (Idilli et al, 2013). The growth of gymnosperm pollen tubes is inhibited by MT-depolymerizing drugs (Anderhag et al, 2000;Justus et al, 2004). In growing root hairs, the loss of MTs leads to wavy growth and bifurcated tips (Bibikova et al, 1999).…”
Section: Introductionmentioning
confidence: 99%